Viola austroyunanensis (Violaceae), a new species from Yunnan province of China - Liao, Shu-Yuan; Liao, Jun-Jie; He, De-Ming; Wu, Jian-Yong; Chen, You-Sheng (Phytotaxa, 2023)
Viola austroyunnanensis is described and illustrated as a new species from southeastern Yunnan province of China. According to morphological studies, it belongs to Viola sect. Diffusae, and is related to V. fargesii, from which it differs by its stolons, petioles, stipules, abaxial leaf surface and sepals being all glabrous (vs. white puberulous), later petals glabrous (vs. beard), flower color usually blue-purple (vs. white); corolla throat nearly white (vs. yellow). But molecular phylogenetic results based on ITS dataset show that V. austroyunnanensis belongs to Viola sect. Adnatae. The systematic relationship of V. austroyunnanensis needs further research.